1992
DOI: 10.1007/bf01246563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach in spider mites (Acari: Tetranychidae): Preliminary data on ribosomal DNA sequences

Abstract: DNA sequence data were used to examine phylogenetic relationships between six species of economically important Tetranychidae mites: Eotetranychus carpini (Oudemans), E. pruni (Reck), Tetranychus pacificus McGregor, T. mcdanieli McGregor, T. turkestani Ugarov & Nikolski and T. urticae Koch. With primers directed toward conserved elements flanking the target region, the Polymerase Chain Reaction was used to amplify the ITS2 spacer of the ribosomal DNA molecule. The nucleotide sequence of a 300-bp fragment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 21 publications
0
25
0
3
Order By: Relevance
“…In what was perhaps the first ever use of molecular phylogenetics in mites, Navajas et al (1992) used primers in the 5.8S and 28S rDNA genes to amplify the ITS2 region in several species of tetranychid mites and showed that this region is suitable for examining phylogenetic relationships within genera, but that differences between genera were too great to enable correct alignment of the sequences. The relationships within the genus Tetranychus agreed closely with morphology but sequences from two sympatric species of Eotetranychus from different hosts, which appeared morphologically very similar except for a slight difference in the shape of the peritreme, showed substantial genetic divergence.…”
Section: Its2mentioning
confidence: 99%
“…In what was perhaps the first ever use of molecular phylogenetics in mites, Navajas et al (1992) used primers in the 5.8S and 28S rDNA genes to amplify the ITS2 region in several species of tetranychid mites and showed that this region is suitable for examining phylogenetic relationships within genera, but that differences between genera were too great to enable correct alignment of the sequences. The relationships within the genus Tetranychus agreed closely with morphology but sequences from two sympatric species of Eotetranychus from different hosts, which appeared morphologically very similar except for a slight difference in the shape of the peritreme, showed substantial genetic divergence.…”
Section: Its2mentioning
confidence: 99%
“…Trabalhos envolvendo a combinação de caracteres morfológicos, estudos biológicos e moleculares também vêm sendo realizados no estudo de ácaros da família Tetranychidae (Navajas et al, 1992(Navajas et al, , 1994(Navajas et al, e 1997.…”
Section: Introductionunclassified
“…A correta identificação dos agentes de controle biológico a serem introduzidos em uma nova área é fundamental, já que identificações imprecisas podem resultar em insucessos (Moraes, 1987 Croft, 1970;Hoying & Croft, 1977;McMurtry, 1980;Navajas et al, 1992Navajas et al, , 1994Navajas et al, e 1997.…”
Section: Introductionunclassified
See 2 more Smart Citations